Role of HLA Adaptation in HIV Evolution - Kløverpris, Henrik N.; Leslie, Alasdair; Goulder, Philip (Frontiers in Immunology, 2016)
Killing of HIV-infected cells by CD8+ T-cells imposes strong selection pressure on the virus towards escape. The HLA class I molecules that are successful in mediating some degree of control over the virus are those that tend to present epitopes in conserved regions of the proteome, such as in p24 Gag, in which escape also comes at a significant cost to viral replicative capacity. In some instances, compensatory mutations can fully correct for the fitness cost of such an escape variant; in others, correction is only partial. The consequences of these events within the HIV-infected host, and at the population level following transmission of escape variants, are discussed. The accumulation of escape mutants in populations over the course of the epidemic already shows instances of protective HLA molecules losing their impact, and in certain cases a modest decline in HIV virulence in association with population-level increase in mutants that reduce viral replicative capacity.